Health Care Reform Simplified What Professionals in Medicine, Government, Insurance, and Business Need to Know - Parks, Dave.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
Health Care Reform Simplified: What Professionals in Medicine, Government, Insurance, and Business Need to Know describes the Patient Protection and Affordable Care Act of 2010. Now that the U.S. Supreme Court has upheld the individual mandate and other key parts of the law$1 (Bwhat must busy healthcare professionals, insurance industry professionals, business and HR managers, and policymakers do? First, read this book. It translates the law$1 (Bs complex language into terms that are easy to understand, explaining what the new law does, when its provisions take effect, and how to implement it. This brand-new second edition also updates all the provisions and explains the myriad ways the ACA is already being put into practice. Health Care Reform Simplified, Second Edition, outlines the financial impact of the law and how it affects businesses, insurers, hospitals and doctors, and state and local governments. Most important, this book gives consumers and employers critical information for making informed choices about new options for private and public health insurance coverage. It also describes how the law interacts with Medicare and Medicaid. Finally, it looks at the potential roadblocks$1 (Bpolitical, judicial, and economic$1 (Bthat may yet derail some of the provisions. But with more than half of the Act's provisions in force already, and the Supreme Court's landmark decision upholding the law, there is no time to lose in understanding how the legislation affects you whether you are a consumer or deliverer of health care in the U.S. This book: Explains health reform in easy-to-understand terms Shows how the law is playing out in the real world Explains the ways the law or parts of it yet may be repealed by the 2012 election and the implications for readers Provides HR professionals and managers options for covering employees while explaining costs and benefits Details the impact on medical professionals and insurers and steps they must take now to comply with the law Shows policymakers the way forward now that legal challenges have abated This edition, completely updated to incorporate the newest regulations and the practices that have been put into place in various states, will prove an indispensable guide for those implementing the law, as well as those receiving health care, in the coming years.s
Keywords: Economics; Economics/Management Science; Business/Management Science, general